Magnetic properties and thermal behavior of the monolayer Rubrene-like nano-island: Monte Carlo simulations. (1st March 2023) - Saber, N.; Fadil, Z.; Mhirech, A.; Kabouchi, B.; Bahmad, L.
Abstract: The magnetic properties of a mixed Rubrene-like nano-island have been extensively investigated using Monte Carlo simulations (MCs) using the Metropolis algorithm in the context of the Blume Capel model. The ground state phase diagrams have been established to display the more stable spin configurations. The effects of various physical parameters on compensation and transition temperatures have been studied. Additionally, triple loops have been found by exploring the hysteresis cycles, which is useful in many applications in multistate memory systems. Highlights: We study the magnetic properties of the Rubrene-like nano-island. The ground state phase diagrams are presented and discussed. The magnetic properties of the Rubrene-like nano-island structure using Monte Carlo simulations are investigated. The hysteresis cycle of the Rubrene-like nano-island structure is analyzed.